ß-alanine supplementation`s improvement of high-intensity game activities in water polo - Pinheiro Brisola, G. M.; de Souza Malta, E.; Pereira Santiago, P. R.; Palucci Vieira, L. H.; Moura Zagatto, A. (International Journal of Sports Physiology and Performance, 2018)
Objectives: To investigate whether 4 wk of ß-alanine supplementation improves total distance covered, distance covered and time spent in different speed zones, and sprint numbers during a simulated water polo game. Design: Double-blind, parallel, and placebo controlled. A total of 11 male water polo players participated in the study, divided randomly into 2 homogeneous groups (placebo and ß-alanine). Methods: The participants performed a simulated water polo game before and after the supplementation period (4 wk). They received 4.8 g/d of dextrose or ß-alanine on the first 10 d and 6.4 g/d on the final 18 d. Results: Only the ß-alanine group presented a significant improvement in total sprint numbers compared with the presupplementation moment (PRE=7.8 [5.2] arbitrary units [a.u.]; POST=20.2 [7.8] a.u.; P=.002). Furthermore, ß-alanine supplementation presented a likely beneficial effect in improving total distance covered (83%) and total time spent (81%) in speed zone 4 (ie, speed=1.8 m/s). There was no significant interaction effect (group×time) for any variable. Conclusions: Four weeks of ß-alanine supplementation slightly improved sprint numbers and had a likely beneficial effect on improving distance covered and time spent in speed zone 4 in a simulated water polo game.